Investigation of defect nucleation in titanium under mechanical loading - Zolnikov K. P.; Korchuganov A. V. Aleksandr; Kryzhevich D. S. Dmitrij; Psakhie S. G. Sergey Grigorievich (2014, 2014)
Title screen